Investigating Writing Performance and Institutional Supports Among Teacher Candidates Who Transferred from Community Colleges - Katharine Pace Miles; Leslie Craigo; Selenid Gonzalez-Frey (Laureate Education Inc, 2018)
To provide a snapshot of the skills of community college students as compared to senior college students, this study investigated writing performance and college experience of initial two-year enrolled (community college transfer students, n = 17) versus initial four-year enrolled students (n = 12) in a teacher preparation program. Results of independent samples t-tests on in-class writing, research paper, and final score were non-significant (p =.28, p = .54, p = .15, respectively) indicating that two-year and four-year start teacher candidates did not differ in their performance on these assignments nor overall in the course. Qualitative data indicated that while both two- and four-year start teacher candidates had a positive writing identity during their first two years of college, the personal support that two-year starts had may be what enabled them to succeed and have a positive writing identity once they transferred to a four-year college. Implications regarding how to coordinate supports for transfer student teacher candidates will be discussed, as this is the very population of diverse students needed as PreK-12 teachers.